Manajemen Risiko dalam Hukum - Nifta Lestari; Nabilah (Cashless : Journal of Sharia Finance and Banking, 2025)
Risk management is a crucial element in the continuity of a company's business amidst increasing complexity and uncertainty. This research uses qualitative literature study methods to analyze the importance of implementing risk management, especially legal aspects, in protecting companies from potential losses due to lawsuits and regulatory violations. By identifying and analyzing legal risks, companies can formulate effective mitigation strategies, such as developing internal policies and employee training. However, challenges such as regulatory complexity and implementation costs often hinder companies, especially small and medium-sized businesses. The use of information technology in risk management and support from top leadership is expected to increase effectiveness and legal awareness in the organization. The research results show that implementing systematic legal risk management not only prevents problems, but also strengthens a company's reputation and increases stakeholder trust.